Eu3+ doped polyphosphate-aminosilane organic-inorganic hybrids - Dias, F. A.; Ribeiro, SJL; Goncalves, R. R.; Messaddeq, Younes [UNESP]; Carlos, L. D.; Bermudez, V. D.; Rocha, J. (Elsevier B.V., 2004)
The preparation and characterization of new Eu3+ doped polyphosphate-aminosilane hybrids xerogels is reported. Eu3+ D-5(0) emission quantum efficiency ranges from 0.41 to 0.54 depending on the SUP ratio. These rather high values are due to the substitution of phosphate and amino groups for water in the Eu3+ coordination shell. Raman and Si-29 and C-13 CP-MAS NMR results suggest that no strong interaction exists between the polyphosphate and the siloxane parts. Not fully condensed siloxane colloidal domains seem to be homogeneously distributed in the polyphosphate network. Good optical quality and favorable Eu3+ spectroscopic characteristics suggest these new hybrids as good hosts for lanthanide ions in optical devices. (C) 2003 Published by Elsevier B.V.
Keywords: organic-inorganic hybrids; sol-gel; europium; polyphosphate; luminescence